Recreational Harvesting of the Florida Bay Scallop: Steinhatchee and Keaton Beach areas, Taylor County - Victor J. Blanco (EDIS)
A full-color map identifying access routes to the boat ramps and marinas in southern Taylor County near Steinhatchee and Keaton Beach, plus the latest information on scallops and scalloping, the recommended equipment you will want to bring, and a few tasty recipes for preparing Florida’s best summertime catch. https://edis.ifas.ufl.edu/sg146